An immunohistochemical method for the diagnosis of melioidosis - Wong, K.T.; Vadivelu, J.; Puthucheary, S.D.; Tan, K.L. (Faculty of Medicine, University of Malaya, 1996)
In order to assess the usefulness of immunohistochemistry in the diagnosis of melioidosis, an infection by Burkholderia pseudomallei, polyclonal antibodies were applied to tissues from known cases of melioidosis and to other infected tissues. Formalin-fixed, paraffin-embedded tissues were stained by a modified immunoperoxidase technique. In autopsy tissues with inflammatory lesions of melioidosis, the cytoplasm of phagocytes and intact bacilli, both intra- and extracellular, were stained very strongly positive. Relatively more focal positive staining was observed in some but not all surgical biopsies from proven cases of melioidosis. In granulomas staining was mainly found in the central necrotic areas, with little staining of peripheral phagocytes. All control materials stained negative. Immunohistochemistry appears to be a useful diagnostic tool in melioidosis.